The impact of upper tropospheric temperatures and radiation on idealized tropical cyclones - Trabing, Benjamin, author; Bell, Michael, advisor; Chiu, Christine, committee member; Suryanarayanan, Siddharth, committee member (Colorado State University. Libraries, 2018)
Potential intensity (PI) theory predicts that the tropopause temperature acts as a powerful constraint on tropical cyclone (TC) intensity and structure. The physical mechanisms by which the upper tropospheric thermal structure and radiative forcing impact TC intensity and structure have not been fully explored however, due in part to limited observations and the complex interactions between clouds, radiation, and storm dynamics. Idealized Weather Research and Forecasting (WRF) ensembles were conducted using a combination of three different tropopause temperatures (196, 199, and 202 K) with different radiation schemes (full diurnal radiation, longwave only, and no radiation) on weather timescales. The simulated TC intensity and structure were strongly sensitive to colder tropopause temperatures using only longwave radiation, but were less sensitive using full-radiation and no radiation. The maximum intensity of the longwave only simulations were more sensitive to small boundary layer moisture perturbations in the initial conditions. Colder tropopause temperatures resulted in deeper convection, increased ice mass aloft, and when radiation was included more intense storms on average. Deeper convection led to increased local longwave cooling rates but reduced top of atmosphere outgoing longwave radiation, such that from a Carnot engine perspective, the radiative heat sink is reduced in the stronger storms. It is hypothesized that a balanced response in the secondary circulation described by the Eliassen equation arises from upper troposphere radiative cooling/heating anomalies that leads to stronger tangential winds. The results of this study further suggest that cloud-radiative feedbacks have a non-negligible impact on weather timescales.
Keywords: radiation; upper troposphere; tropical cyclones; potential intensity